Brand Engagement Optimization: A Digital Marketing Approach in Changing Public Perception of the Directorate General of Customs and Excise - Yogi Darminto (Jurnal Indonesia Sosial Teknologi, 2024)
This study aims to analyze the effectiveness of digital marketing strategies in increasing public perception of the Directorate General of Customs and Excise (DJBC) of Indonesia. As an important institution in national economic stability, DJBC has a dual role as a collector of state revenue, a trade facilitator, and an industry supporter. However, public trust in the DJBC has been affected by various negative factors. To improve its brand image, DJBC launched the "Makin Baik" campaign which utilizes digital marketing techniques. The study examines the impact of three main components: brand campaign effectiveness, digital content quality, and posting frequency consistency on public perception. A mixed method was used in this study, combining qualitative case studies and quantitative surveys. The results showed a significant increase in public trust from 45% in 2022 to 60% in 2023, due to the increase in DJBC's digital engagement and content strategy. Additionally, social media analytics showed an increase in engagement and follower counts, signaling the campaign's success in attracting public attention. Despite this, DJBC still faces challenges in overcoming negative stigma and ensuring a sustainable digital communication strategy. This research contributes to the understanding of optimizing brand engagement for government institutions through digital marketing.